Study the effect of Different Levels of Curcuma longa on Some Physiological and Specific Egg Traits and Intestinal Environment for Quail - Ghadeer AL- Rahawi (Basrah Journal of Veterinary Research)
The aim of the current study was to evaluate the effect of different levels of Curcuma longa on some physiological and biochemical parameters, as well as some egg productive and quality characters and the intestinal microflora of local quail. 240 one-day-old quail were distributed randomly into 4 groups (60 birds/group) with 3 replicates. The groups were as follows: 1st group (control) birds were reared on standard ration, the 2nd, 3rd and 4th groups birds were reared on standard ration supplemented with 3, 6 and 9 gm turmeric/kg ration respectively. The results revealed that the turmeric improve blood picture as represented by the significant increase of RBCs, Hb and PCV% specially in 3rd and 4th treatments. Also, the turmeric reduced significantly triglycerides and cholesterol compared with the control. Curcuma longa treatment improved the intestinal microflora represented by the significant decrease in the number of pathogenic flora (Salmonella and E. coli), and significant increase in the benefit flora (Lactobacillus). On the other hands treatments reduced significantly the age of 1st egg production and enhance the age of 50% egg production. In conclusion, Curcuma longa treatment induced ameliorative effects on some of physiological and productive performance of quail.